Analisis Pengaruh Kinerja Keuangan Pemerintah Daerah Terhadap Belanja Modal Untuk Pelayanan Publik: Studi Pada Pemerintah Provinsi, Kabupaten Dan Kota Di Provinsi Riau - Ramdhany, Muhammad; Karneli, Okta; Othman, Lie (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
This research is motivated by the phenomenon of regional government in Indonesia that has not fully optimized the regional financial performance. The good financial performance of a government in the region can be seen through how the government in the region regulates and manages its Regional Budget and Expenditures (APBD) which are used to provide financing for development needs and activities in the region. Performance from a financial perspective that is going well and is progressing will be directly proportional to the increase in regional income. This means that there is efficiency and effectiveness of the working power of finance in local governments. There is an increase in the working power of the finances will bring the existing government in the region to be able to optimize the allocation of capital expenditure in order to fulfill regional development and have an impact on improving the quality of public services. The purpose of this study is to analyze the working power of Regional Government finances, both Provinces, Regencies and Cities in the region of Riau Province by measuring the level of Efficiency Effectiveness of Regional Original Revenue, Regional Finance, Degree of Fiscal Decentralization, independence from Finance in the Region , as well as the SiLPA Financing Rate. The results of the study show that the working power of Regional Finance in the form of Regional Financial Efficiency, Effectiveness of Local Own Revenue, Degree of Fiscal Decentralization, independence from Regional Finance, and Level of SiLPA Financing jointly influence and have significance for spending from capital for Public Services. Partial Financial Independence in the Regions does not have significance nor influence in the context of Capital Expenditures for Public Services. The effectiveness of Regional Own Revenue partially has no significance and also influences Capital Expenditures for Public Services. The efficiency of Regional Finance partially has significance and also influences on Capital expenditures for Public Services. And the level of SiLPA financing partially has no significance and also no influence on capital spending for public services.